Synthesis and Antimicrobial Activity of Newer Quinazolinones - J. A. Patel; B. D. Mistry; K. R. Desai (E-Journal of Chemistry)
2–alkyl–6–bromo–3,1–benzoxazine–4–one (2) is synthesized by treating p–Bromoanthranilic acid and Acetylechoride or Benzoylchloride. Reaction of 2–alkyl–6–bromo–3,1–benzoxazine–4–one (2). with hydrazinehydrate furnish the corresponding 3–Amino–2–methyl–6–bromoquinazoline–4(3H)–one (3) which on reaction with benzaldehyde afford N,N – arylidene derivative (4). Reaction of 4 with various diazonium salts yields 6–bromo–2–alkyl/aryl–3{[phenyl(phenyldiazenyl)methylene]amino}quinazolin–4(3H)–one .